Gender power, fertility, and family policy - Alexander Kemnitz; Marcel Thum (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2013)
The birth of children often shifts the power balance within a family. If family decisions are made according to the spouses' welfare function, this shift in power may lead to a time consistency problem. The allocation of resources after the birth of children may differ from the ex-ante optimal choice. In a model of cooperative decision making within a family, we show that this time consistency problem leads to a systematic downward bias in fertility choices. By keeping fertility low, families try to mitigate the ex-ante undesired shift in the power balance. This bias in fertility choices provides scope for welfare enhancing policy intervention. We discuss the extent to which existing measures in family policy are suitable to overcome the fertility bias.
Keywords: D13; H31; J13; 330; Fertility; Family Policy; Household Allocation